Monitoring Konsumsi Energi kWh 3 Phasa Secara Real Time Dengan Aplikasi Amicon - Zidane, M. Zinedine; Anisah, Siti; Pengalaman Tarigan, Adisastra (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2025)
Postpaid energy meter billing still often uses conventional methods in most areas of PT. PLN (Persero), involving personnel to manually read meters and collect data physically. This process includes visiting customers' homes to collect data, take photos, and deliver bills directly. The weaknesses of this method include potential inaccuracies in readings and the risk of data manipulation by personnel. To improve efficiency and accuracy, the Automatic Meter Reading (AMR) system has been introduced. AMR allows for remote reading and monitoring of energy consumption through communication media, reducing the need for direct interaction and minimizing errors and data manipulation. This system also facilitates the detection of electricity theft and energy losses, which can be caused by technical issues or illegal electricity use. Based on the results of the research carried out, there has been a voltage drop of 121.4 Volts or 51% of the nominal/transmit voltage caused by the kWh input terminal being damaged. The implementation of AMR technology in 3-phase kWh meters is expected to improve reading accuracy, reduce losses, and enhance customer satisfaction by providing real-time and automatic consumption data.